Higher School Teacher's Competences and "Electronic" Pedagogical Culture in the Post-Pandemic World - T. E. Isaeva (Moscow Polytechnic University, 2021)
During the period of the forced remote learning caused by the threat of the coronavirus infection spread, Russian university teachers, as well as their foreign colleagues, had to acquire quickly new skills in the field of information technologies and organization of classes exclusively in electronic mode. However, the changes in the structure of the teachers' personality were not limited only to informational and methodological competences. The relevance of this research is to test the hypothesis about the emergence of a new type of teacher's pedagogical culture, characterized by a special awareness of the humanistic and social role of a teacher in the course of e-learning. The aim is to study the content of a new type of pedagogical culture, as well as its structural components performed by the competences, the presence of which was actualized during the pandemic. The theoretical research methods (study and analysis of scientific publications on the teachers' competences, especially in demand during the pandemic, synthesis, systematization, comparison, etc.) and empirical methods (conversation, questioning, observation) were used in the study. The conducted empirical research, as well as the analysis of domestic and foreign publications show that, despite a short-term nature of remote learning, the transformations in pedagogical culture have the character of a qualitative leap and are global in nature, as they have affected the teachers in all countries. This allows us to declare the emergence of a new type of pedagogical culture, namely the "electronic" pedagogical culture of a higher school teacher, which is a natural result of the development of "basic" culture and is characterized by a change in priorities in the structure and in the content of its constituent blocks of competences. The article compares real changes in the structure of a teacher's personality with forecasts regarding the "competences of the future", as well as with the "information pedagogical culture", which is believed to have arisen in the process of information technologies penetration into the educational process. The scientific novelty of the research consists in substantiating the possibility of transforming the "basic" pedagogical culture of the teacher under the influence of external and internal factors. In theoretical terms, the study expands the scientific understanding of the essence of the teacher's pedagogical culture, the patterns of its development and transformation, as well as its competence-based structural organization.